Analisis Peneguhan Jati Diri Berkomitemen Kebangsaan Peserta Didik Melalui Moderasi Beragama - Alfrida Pasorong; Yohanis Salama; Frans Fandy Palinoan (Departement of Mathematics Education, 2021)
This study aims to analyze the affirmation of national commitment through religious moderation for students. In this study the authors used qualitative research methods with literary and argumentative review techniques. The results of this study indicate that in the world of education, as a student one must be able to balance obligations as a religious community and also as an Indonesian citizen. This realization can be realized through national holiday activities, for example becoming a paskibraka, participating in commemorating national holidays, participating in the Olympics, participating in extracurricular scouting etc.